Implementasi Sistem Pemberian Pakan Ikan Hias Otomatis Menggunakan Esp32 Berbasis IoT (Internet of Things) - Sugiarto, Muhammad Aqsha Rizki; Muhtarom, Moh; Asri, Anindhiasti Ayu Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study aims to design and implement an automatic feeding system for ornamental fish using Internet of Things (IoT) technology, with the ESP32 microcontroller and servo motor. Given Indonesia's extensive water resources and the importance of its fisheries sector, ornamental fish farming has gained significant popularity. Fish owners often struggle with providing timely and consistent feeding. IoT technology offers an effective solution through remote connectivity. The developed system utilizes the Blynk application to schedule and monitor aquarium conditions in real-time. Test results indicate that the integration of ESP32 and the servo motor functions effectively, enabling scheduled automatic feeding. The system was tested and found to operate punctually, supporting a consistent daily feeding cycle. This study contributes to the advancement of innovative solutions in aquaculture, particularly in the application of IoT technology for more efficient and effective aquarium management.